The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s13191-013-0331-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating The Fracture Toughness and Flexural Strength of Pressable Dental Ceramics: An In Vitro Study

Abstract: The study was undertaken to evaluate the biaxial flexural strength, biaxial flexural strength after etching with 9 % HF acid and fracture toughness of three commonly used pressable all ceramic core materials. Ninety glass ceramic specimens were fabricated from three commercially available leucite based core ceramic material (1) Esthetic Empress, (2) Cergo, and (3) Performance Plus. Thirty discs of each material were divided into three groups of 10 discs each. Biaxial flexural strength (30 discs,) Biaxial flexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…2,3,5 Therefore, the use of glass-ceramic material with improved flexural strength (>120 MPa) is recommend for the fabrication of ceramic veneers for these high-risk indications (remaining enamel: 50% or less). [18][19][20][21][22] Nevertheless, studies focusing on extended ceramic veneers with larger areas of exposed dentin that enable a risk analysis are still sparse. 18,19 Given that these data were generated in a university setting in a prospective clinical trial under standardized conditions, it is unclear how successful this treatment concept will be in the typical private practice environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,5 Therefore, the use of glass-ceramic material with improved flexural strength (>120 MPa) is recommend for the fabrication of ceramic veneers for these high-risk indications (remaining enamel: 50% or less). [18][19][20][21][22] Nevertheless, studies focusing on extended ceramic veneers with larger areas of exposed dentin that enable a risk analysis are still sparse. 18,19 Given that these data were generated in a university setting in a prospective clinical trial under standardized conditions, it is unclear how successful this treatment concept will be in the typical private practice environment.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that more extensive veneer restorations would benefit from the higher mechanical strength of glass–ceramics, as higher tensile and shear stresses occur when there are large areas of unsupported porcelain or when bonding to more flexible substrates such as dentin . Therefore, the use of glass–ceramic material with improved flexural strength (>120 MPa) is recommend for the fabrication of ceramic veneers for these high‐risk indications (remaining enamel: 50% or less) . Nevertheless, studies focusing on extended ceramic veneers with larger areas of exposed dentin that enable a risk analysis are still sparse …”
Section: Introductionmentioning
confidence: 99%
“…The fracture toughness values of the specimens co-doped with Tm 2O3 and Er2O3 were 4.27 to 4.64, respectively, which is approximately 4% to 12% lower than the toughness value of 4.83 found in the control samples. However, these values were approximately 3.5 to 3.8 times as high as the fracture toughness of conventional glass ceramics (1.22) 26) . Therefore, the high fracture toughness that characterizes zirconia was maintained.…”
Section: Discussionmentioning
confidence: 75%
“…An important aspect to be taken into consideration when comparing all these results is the fact that most of the available scientific literature[ 9 10 11 12 13 14 15 16 17 18 19 20 ] on zirconia strength uses geometric plane samples that do not reflect the actual configuration of a fixed prosthesis, which has curved lines or uneven material thickness, thus leading to an approach different from the ones applicable in clinical situations.…”
Section: Discussionmentioning
confidence: 99%